Crimean-Congo Hemorrhagic Fever in Differential Diagnosis During the Coronavirus Disease-2019 Pandemic - Sağmak Tartar, Ayşe; Akbulut, Ayhan; Demirdağ, Kutbeddin; Balin, Şafak Özer (Galenos Publishing House, 2022)
Objective: Crimean-Congo Hemorrhagic Fever (CCHF) is a disease of the viral hemorrhagic fever group and is endemic in certain regions in Turkey. Here, the demographic, clinical, and laboratory findings of patients diagnosed with CCHF during the Coronavirus disease-2019 (COVID-19) pandemic were examined, and differential diagnosis was stressed. Methods: This study comprised 12 patients over the age of 18 who were admitted to our clinic after the onset of the COVID-19 pandemic on March 11, 2020 and whose CCHF diagnosis was confirmed by reverse transcription-polymerase chain reaction with viral-RNA or enzyme-linked immunosorbent assay with immunoglobulin M antibodies. Epidemiological, clinical, and laboratory findings as well as treatment and prognosis of the patients were investigated. Results: Of the 12 cases, 10 (83.3%) were men and 2 (16.7%) were women. The median (interquartile range) age was 51 (27-64) years. Eleven (91.7%) patients lived in rural regions, and seven (58.3%) had a history of tick contact. Five patients were hospitalized in an external center with a preliminary diagnosis of COVID-19 and transferred to our center due to clinical and laboratory deterioration. Loss of appetite, headache, fever, weakness, and muscle-joint pain were the most common complaints of the patients. Following the suspicion of COVID-19, thoracic computed tomography (CT) was performed in six patients, five of whom were transferred to an external center. None of the patients had any pathological findings following thoracic CT. Conclusion: Although it is thought that the COVID-19 pandemic will end in the following months owing to vaccine applications, it can be predicted that sporadic cases will still occur for a long time. Therefore, clinicians should take CCHF into consideration in their differential diagnosis. Also, it should be remembered that co-infections can be observed in endemic areas. © 2022, Galenos Publishing House. All rights reserved.
Koronavirüs Hastalığı-2019 Pandemisinde Ayırıcı Tanıda Akılda Tutulması Gereken Hastalık: Kırım-Kongo Kanamalı Ateşi
Keywords: COVID-19 pandemic; Crimean-Congo Hemorrhagic Fever; lymphopenia; tick